UNIT KEPATUHAN DAN AUDIT INTERNAL BANK SYARIAH DI INDONESIA; SUDAHKAH SESUAI DENGAN PRINSIP SHARIAH GOVERNANCE? - Arrazi, Muhammad Fakhrul (IAIN Tulungagung, 2021)
Shariah governance is crucial in the Islamic banking system to ensure that all commercial operations comply with Islamic principles and differentiate Islamic banking operations from conventional banking. This research discusses the similarities between the practice of the compliance unit and internal audit of Islamic banks in Indonesia and Bank Indonesia/ OJK’s regulations and existing standards. The data for the research were collected through interviews and documentation instrument, and analyzed by using qualitative methods. Based on the analysis, the researcher identified that the work practices of the compliance unit and internal audit of Islamic banks in Indonesia are in line with regulations promoted by Bank Indonesia/ OJK, AAOIFI and IFSB shariah governance, but are still not comprehensive when compared to the Shariah governance framework of Bank Negara Malaysia and the opinions of other practitioners of Islamic Economics.